Implementasi Google Sites Dalam Manajemen Pengelolaan Kinerja PPNPN (Pegawai Pemerintah Non Pegawai Negeri): Studi Kasus Penerapan Aplikasi Situ PPNPN Pada Kanwil DJBC Jateng dan D.I. Yogyakarta - Saputro, Riko Fajar; Tarigan, Djoesept Harmat (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Non-Civil Servant Government Employees (PPNPN) are a vital component in the operational activities of an organization. However, their performance management faces challenges in efficiency and standardization. This scientific paper examines the potential implementation of Google Sites as a platform for PPNPN performance management. The analysis focuses on the existing regulatory framework. The proposed model leverages the integration of Google Sites with Google Forms, Google Sheets, and other supporting applications provided by Google to digitize the performance management cycle, from planning, monitoring, and evaluation (based on indicators such as integrity, discipline, teamwork, communication, and service), to documentation and feedback. The main advantages of this platform include administrative efficiency, increased data transparency and accessibility, centralized data management, potential for consisten process, collaboration, and cost-effectiveness. Nevertheless, its implementation faces significant challenges related to the digital literacy gap among PPNPN with diverse roles, data security and privacy issues in the public sector, the need for robust change management, feature limitations compared to specialized HRIS systems, particularly in the Ministry of Finance where the research object's office is located, and the necessity for adequate supporting infrastructure. This research concludes that Google Sites offers a technically viable solution, but its success highly depends on the organizational and human resource readiness of both the HR managers and the PPNPN themselves.